2019
DOI: 10.1111/aspp.12496
|View full text |Cite
|
Sign up to set email alerts
|

What Threat? Leadership, Strategic Culture, and Indonesian Foreign Policy in the South China Sea

Abstract: Why is there no balancing behavior in Southeast Asia vis‐à‐vis what many observers see as a “Chinese threat,” especially in the case of Indonesia? Despite all the concerns regarding the stability of the region, Indonesia is neither strengthening its power projection capability nor building a coalition to address China's growing power in the South China Sea. Indonesia's underbalancing behavior is the result of a strategic culture that influences its military and foreign policy thinking on threat perceptions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Some scholars have already examined how Indonesia's strategic culture hampered the GMF execution. For example, one author suggested that Indonesia's underbalancing behaviour has been the result of a strategic culture that affects its military and foreign policy thinking on threat perceptions (Sulaiman, 2019). Meanwhile, another researcher noted that due to strategic culture, the Indonesian Navy is not allowed to expand its roles (Arif & Kurniawan, 2017).…”
Section: Neoclassical Realismmentioning
confidence: 99%
“…Some scholars have already examined how Indonesia's strategic culture hampered the GMF execution. For example, one author suggested that Indonesia's underbalancing behaviour has been the result of a strategic culture that affects its military and foreign policy thinking on threat perceptions (Sulaiman, 2019). Meanwhile, another researcher noted that due to strategic culture, the Indonesian Navy is not allowed to expand its roles (Arif & Kurniawan, 2017).…”
Section: Neoclassical Realismmentioning
confidence: 99%
“…Of late, some have employed Schweller's model in understanding Indonesia's response towards major and revisionist powers; or argue that Indonesia is either non-balancing or underbalancing (Laksmana, 2016a(Laksmana, , 2016bSulaiman, 2019;Syailendra, 2017). However, reliable empirical differentiation of whether a state is overbalancing, non-balancing or underbalancing, is often difficult to make, particularly, without the benefit of hindsight.…”
Section: Domestic Politics and Foreign Policymentioning
confidence: 99%
“…The articles employing neoclassical realism identify systemic/external stimuli that Indonesia currently faces, highlighting the importance of domestic politics in shaping various stakeholders' perception on such stimuli, as well as in influencing their conception of foreign policy goals and national interest (He, 2008;Korolev & Portyakov, 2018;Kuik, 2012;Laksmana, 2016;Lobell et al, 2009, p. 322;Magcamit, 2020;Meibauer, 2020;Rose, 1998;Sari, 2019;Sebastian & Syailendra, 2017;Smith, 2019;Sulaiman, 2019;Syailendra, 2017). 9 Departing from neorealism, which suggests that states placed in a similar position in the international system would behave similarly despite differing domestic structures, neoclassical realists 'seek to explain variation in the foreign policies of the same state over time or across different states facing similar external constraints' (Taliaferro et al, 2009, p. 21).…”
Section: Foreign and Maritime Policies Through The Lens Of Neoclassical Realism Actor-specific Theory And Decision-making Theorymentioning
confidence: 99%
“…Neoclassical realist scholars emphasise that state behaviour is influenced by domestic political situations when adapting to the external environment (Korolev & Portyakov, 2018;Kuik, 2012;Lobell et al, 2009;Magcamit, 2020;Meibauer, 2020;Rose, 1998;Smith, 2019). For an application of neoclassical realism in the study of Indonesia's foreign and security policy, see (He, 2008;Laksmana, 2016;Sari, 2019;Sebastian & Syailendra, 2017;Sulaiman, 2019;Syailendra, 2017).…”
Section: Foreign and Maritime Policies Through The Lens Of Neoclassical Realism Actor-specific Theory And Decision-making Theorymentioning
confidence: 99%